Peran Trait Mindfulness terhadap Fear of Missing Out Pengguna Media Sosial - Laurentius Sandi Witarso (Philanthropy: Journal of Psychology, 2023)
Abstract. Indonesia's increasing internet use has positive and negative impacts on social media users. The positive impact is maintaining communication, but on the other hand, it can lead to FoMO (Fear of Missing Out) which can interfere a person's mindfulness trait. This research aims to analyze the role of the trait mindfulness on FoMO of social media users. This research used  FoMO Scale and Five Facet Mindfulness Questionnaire. Measuring tools are distributed online using the convenience sampling method and it has got a total of 347 participants. The results of the regression test showed that the mindfulness trait dimensions significantly predicted FoMO F = 17.1; p < 0.001, R2 = 0.20 which means that the mindfulness trait has a 20% contribution to the fear of missing out, while the other 80% is influenced by other factors. However, only acting dimensions with awareness and non-judging of inner experience have significant predictive coefficients.Keywords: social media, fear of missing out, trait mindfulnessAbstrak. Meningkatnya penggunaan internet di Indonesia berdampak positif dan negatif bagi pengguna media sosial. Dampak positifnya adalah sebagai sarana untuk menjaga komunikasi, namun di sisi lain dapat memunculkan FoMO (Fear of Missing Out) yang dapat mengganggu trait mindfulness individu. Tujuan penelitian ini adalah untuk menganalisis peran trait mindfulness terhadap FoMO pengguna media sosial. Alat ukur yang digunakan adalah FoMO Scale dan Five Facet Mindfulness Questionnaire. Alat ukur disebar melalui daring dengan metode convenience sampling dan didapatkan partisipan sebanyak 347 orang. Hasil uji regresi menunjukkan dimensi-dimensi trait mindfulness memprediksi FoMO secara signifikan F = 17,1; p < 0,001, R2 = 0,20 yang berarti trait mindfulneess memiliki pengaruh kontribusi sebesar 20% terhadap fear of missing out sedangkan sebesar 80% lainnya dipengaruhi oleh faktor-faktor lain selain trait mindfulness. Namun demikian hanya dimensi acting with awareness dan non-judging of inner experience yang memiliki koefisien prediksi signifikan. Kata kunci : media sosial, fear of missing out, trait mindfulness